2021
DOI: 10.3389/fvets.2021.779298
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Neurotrophin-4 Supplementation During in vitro Maturation of Porcine Cumulus-Oocyte Complexes and Subsequent Embryonic Development After Parthenogenetic Activation

Abstract: Neurotrophin-4 (NT-4) is a neurotrophic factor that plays an important role in follicular development and oocyte maturation. However, it is not yet known whether NT-4 is related to oocyte maturation and follicular development in pigs. This study aims to investigate the effects of NT-4 supplementation during in vitro maturation (IVM) of porcine oocytes and subsequent embryonic development after parthenogenetic activation (PA). First, NT-4 and its receptors (TrkB and p75NTR) were identified through fluorescent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…In mice, the NGFR mRNA is expressed in all follicular cells (mural granulosa cells and CCs), except oocytes ( Kawamura et al, 2005 ); in cattle, the p75 NTR mRNA ( Da Silva et al, 2005 ) and protein ( Levanti et al, 2005 ) are expressed in both oocytes and CCs. In porcine studies, both p75 NTR mRNA ( Lee et al, 2007 ; Kim et al, 2021 ) and protein ( Levanti et al, 2005 ; Kim et al, 2021 ) have been detected in all follicular cells (granulosa cells, CCs, and oocytes). In our previous study, NT-4-related signaling pathways were identified in response to the MAPK/ERK pathway in matured porcine COCs by qPCR analysis ( Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In mice, the NGFR mRNA is expressed in all follicular cells (mural granulosa cells and CCs), except oocytes ( Kawamura et al, 2005 ); in cattle, the p75 NTR mRNA ( Da Silva et al, 2005 ) and protein ( Levanti et al, 2005 ) are expressed in both oocytes and CCs. In porcine studies, both p75 NTR mRNA ( Lee et al, 2007 ; Kim et al, 2021 ) and protein ( Levanti et al, 2005 ; Kim et al, 2021 ) have been detected in all follicular cells (granulosa cells, CCs, and oocytes). In our previous study, NT-4-related signaling pathways were identified in response to the MAPK/ERK pathway in matured porcine COCs by qPCR analysis ( Kim et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In porcine studies, both p75 NTR mRNA ( Lee et al, 2007 ; Kim et al, 2021 ) and protein ( Levanti et al, 2005 ; Kim et al, 2021 ) have been detected in all follicular cells (granulosa cells, CCs, and oocytes). In our previous study, NT-4-related signaling pathways were identified in response to the MAPK/ERK pathway in matured porcine COCs by qPCR analysis ( Kim et al, 2021 ). In the current study, the relative mRNA expression levels of NGFR and its downstream gene, NFKB1 , were analyzed in matured porcine COCs upon NT-4 treatment during IVM to confirm the involvement of the NT-4/p75 NTR -related signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations